RANGKAIAN PENYEARAH SETENGAH TERKENDALI TIGA FASA UNTUK PENGENDALIAN KARAKTERISTIK MOTOR ARUS SEARAH SHUNT - Ahmad Antares Adam (Foristek, 2011)
A modern control of electric motor’s speed in an industry needs a variable direct voltage. The variable direct voltage can be supplied by semiconductor devices such as SCR. The output voltage of a SCR rectifier depends on the delay angle of theSCR. The aim of this research is to make a SCR rectifier circuit and applying it for observing the characteristics of a shunt directcurrent motor. The result shows the circuit can work to demonstrate the shunt motor characteristics.